1990
DOI: 10.1111/j.1467-8624.1990.tb02768.x
|View full text |Cite
|
Sign up to set email alerts
|

Child-Mother Attachment of Six-Year-Olds and Social Competence at School

Abstract: 89 children and their mothers participated in a study examining the association between attachment and peer social competence. During the summer following kindergarten, quality of attachment was assessed from reunion episodes following a 1-hour separation. In the fall, measures of sociometric status, peer behavior nominations, and peer liking ratings were collected. Teachers completed liking ratings and ratings of behavior problems and competence. Consistent with longitudinal studies of infant attachment and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
80
0
15

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(106 citation statements)
references
References 22 publications
10
80
0
15
Order By: Relevance
“…Of note, after teacher-reported social and behavioral skills were entered in the regression models, however, the attachment effect faded. This is likely due to the fact that the effect of attachment on L2 attainment is mediated by the enhanced child social skills that result from stronger attachments (Cohn, 1990). Attachment will be an important construct to explore in future research on the bilingual language development of ELLs, especially given speculation that the parent-child relationship may be in jeopardy if children adopt L2 too quickly and show L1 language loss (Wong Fillmore, 1991) and that some outcomes for immigrant children are enhanced when L1 is spoken in the home (Winsler et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, after teacher-reported social and behavioral skills were entered in the regression models, however, the attachment effect faded. This is likely due to the fact that the effect of attachment on L2 attainment is mediated by the enhanced child social skills that result from stronger attachments (Cohn, 1990). Attachment will be an important construct to explore in future research on the bilingual language development of ELLs, especially given speculation that the parent-child relationship may be in jeopardy if children adopt L2 too quickly and show L1 language loss (Wong Fillmore, 1991) and that some outcomes for immigrant children are enhanced when L1 is spoken in the home (Winsler et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The interactions that occur through play tell children that parents are fully paying attention to them and help to build enduring relationships. 6,13,14,20,21 Parents who have the opportunity to glimpse into their children's world learn to communicate more effectively with their children and are given another setting to offer gentle, nurturing guidance. Less verbal children may be able to express their views, experiences, and even frustrations through play, allowing their parents an opportunity to gain a fuller understanding of their perspective.…”
Section: The Benefits Of Playmentioning
confidence: 99%
“…Study NICHD (1997) Shaw et al (1996) Barnettetal (1997) Seifer, Schiller, et al (1996) Spangieretal ( cal or health problems the combined effect size was r = -12 (n s ), mdicatmg that disorganized attachment is not due to sometimes severe physical problems (brain mjury, cleft palate) In the studies usmg the Main and Solomon (1990) System, the effect size was r = -10 Sex Boys have been suggested to be more liable to develop disorganized attachment behaviors than girls (Lyons-Ruth et al, 1997) äs they seem to be more vulnerable to environmental nsks in general (Benenson, 1996) In Table 4, 11 studies on sex and disorganized attachment mvolvmg n = 1,858 participants have been listed The combined effect size across these studies was r = -01 (n s) Excluding the study usmg the controlling attachment category for older children (Cohn, 1990), we found a similar absence of an association between sex and disorgamzation The set of study outcomes was heterogeneous, however, χ 2 (10) = 2061, ρ= 02 In particular the rather small study by Carlson et al (1989) on non-maltreated subjects showed an outlymg effect size of r-51 Without this study the set of studies was homogeneous…”
mentioning
confidence: 99%